(3GdJMaI GdSfjI aj TQM GdfNHI GdeMSfjIs - (3GdehShj, GdLRGFQj, YHO Gddg Hf fhQ GdOjf Hf fYeI Gddg Hf YHO Gddg, J (B1173(3g`s
(3ChdgG (B:s
(3Gddge EfG fMeOc MeOG jchf hSjdI dfG Edjc(B...(3CeG HYO(B...(3gPG CjgG GdCN Gdhaj hGdUOjb GdUOhb GdUaj(B...(3ef JYdjbI NajaI Ydi cJGH GdfNHI(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG CKfGA HGH (B((3GdgOjI ddejJ(B) (3bhdI(B: ...(3hde Cba efgG EdG Ydi eG hQO Yf GdfHj Udi Gddg Ydjg hBdg eQSdG bGd(B: ((3dG jCJj Ydi GdejJ SGYI CTO ef Chd djdI(B) ...s
(3JHUQI GdYfhGf (B:s
(3GdJMaI GdSfjI aj TQM GdfNHI GdeMSfjI (B((3ebOeI(B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B304s
(3GdPQjYI(B:(3L(B3(3,U(B241(3,Qbe(B1606s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis